Vrouwen van Amsterdam - van Heye, Claude; Engel, Mattheus; van der Elsken, Ed; Meerum Terwogt, Hanneke (Amsterdam: Foton, 1970)
"Foto's van Ed van der Elsken, Mattheus Engel, Claude van Heye... et al. ; Fotografen geïnterviewd door Hannneke Meerum Terwogt"